Mid-Term Functional and Radiological Outcomes in Patients with Rockwood Type III Acromioclavicular Dislocation Treated with Percutaneous Double Endobutton and Fibre Wire Technique - Kumar Gupta, Mithilesh; Panthee, Rajan; Nepal, Santosh; Kafle, Gokul; Sah, Rajkumar (Nepal Orthopaedic Association Journal, 2024)
Introduction: Surgical treatment for type III ACJ dislocation remains controversial among orthopedic surgeons, with wide options of techniques and devices. Our study aims to review the functional and radiological outcomes after percutaneous fixation for type III acromioclavicular (AC) joint dislocation using the double Endobutton and fiber wire device. Method: In this prospective study, 39 participants were intervened with percutaneous reconstruction of dislocated ACJ. Final evaluation was done by recording the DASH score, VAS, and Constant score and measuring the coracoclavicular (CC) distance before surgery and at the final follow-up (six-month postoperative period). Results: The mean time to return to work was 9.2 (range, 6–12) weeks. The mean final Constant score was 0.67±1.2. The VAS and DASH also diminished significantly by the final follow-up at six months. The CC distance decreased to 9.93±2.2 at six months. In two patients, conversion to open procedure was required. Conclusion: Percutaneous double endo button fiber wire fixation is quick, uncomplicated, and less expensive, with low complications and high functional satisfaction.